Women's experiences of infertility after the Holocaust - Kleinplatz, Peggy J.; Weindling, Paul (Social science & medicine (1982), 2022)
Nuremburg trial evidence demonstrated that Nazis sought methods of mass sterilization of Jewish women. Immediately upon arrival at the concentration camps, over 98% of women stopped menstruating. There has been minimal investigation as to the cause(s) of amenorrhea, beyond malnutrition and trauma. The major objectives of this article are to 1) provide an alternate hypothesis to explain women's amenorrhea, i.e., surreptitious administration of exogenous hormones to women; 2) detail survivors' reproductive histories so as to demonstrate long-term sequellae, especially pregnancy losses; 3) provide women's subjective narratives of the short- and long-term experience of reproductive losses; 4) link women's amenorrhea, subsequent primary and secondary infertility and the evidence for the hypothesized causal mechanism, i.e., the administration of sex steroids which might have led to both immediate and long-term reproductive impacts. We conducted telephone interviews from 2018 to 2021 with Holocaust survivors internationally in 4 languages. We collected 93 testimonies from female Holocaust survivors (average age 92.5) or offspring who could provide complete reproductive histories for survivors. The interviews focused on reproductive histories, including amenorrhea beginning in 1942–45, subsequent attempts to conceive, numbers of pregnancies, miscarriages and stillbirths. Ninety-eight percent of women interviewed were unable to conceive or carry to term their desired number of children. Of 197 confirmed pregnancies, at least 48 (24.4%) ended in miscarriages, 13 (6.6%) in stillbirths and 136 (69.0%) in live births. The true number of pregnancy losses is likely much higher. Only 15/93 (16.1%) of women were able to carry more than two babies to term, despite most wanting more children desperately. Amenorrhea among Jewish women arriving at concentration camps was too uniform and sudden to be effected only by trauma and/or malnutrition. Survivors' narratives and historical evidence suggest the role of exogenous hormones, administered without women's knowledge to induce amenorrhea as well as subsequent primary and secondary infertility. •New testimonies of 93 female Holocaust survivors cover their reproductive histories.•The cause of amenorrhea in the camps might have included administration of hormones.•Survivors had strikingly high rates of primary or secondary infertility after the war.•Subsequent pregnancy losses might have been due to hormones administered in the camps.•Jewish women's narratives as to the meanings of their hidden losses are given voice.